Analysis of pesticide residue of raw goat milk by using GC-MS - Ismail, Nur Maisarah (2020)
Milk is considered as a complete food because of its extraordinary nutritional value. Improper treatment and extensive use of pesticides in farm have resulted in threats to human health and economic loss. In this study, pesticide residue is analysing in goat milk sample by using gas chromatography mass spectrometry (GC/MS). Variety of pesticide has been used in order to control the agricultural pest, but if its presence in milk it will contribute to the serious issue of human health. This study was done checked the amount of pesticide residue in goat milk and ensure goat milk free from pesticides residue or the level below, MRL. The sample of milk is obtaining from goat farm in Kelantan. The extraction of sample will be done by using Solid Phase Extraction (SPE). The pesticides residues were deterMined by through GC/MS. The result of this research shown that the goat milk samples was safe for human use because there are no pesticides were detected. This study contributes information regarding the foods contamination so that Malaysia should make strict rules that will limit and minimise the usage of pesticides.